1986
DOI: 10.1007/bf01389869
|View full text |Cite
|
Sign up to set email alerts
|

Some generalizations of the Euler-Knopp transformation

Abstract: Summary. The purpose of this paper is to construct a generalization of the Euler-Knopp transformation. Using this, one may recover previously known transformations, derive new transformations useful for numerical calculations and derive generating functions and other formulas of theoretical interest involving well-known functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Theorem 3.3 and 3.11 are examples for the application of the transformed series (2.1). Concerning the generality of this approach we observe that the proof of the theorems consists in finding regions of the complex s-plane where the value Popt for series (2.1) is fully determined by certain "key singularities" of f(s) = S(F) and in showing that nothing changes if in these regions there are more singularities of f. Then we note that the cases of Theorems 3.3 and 3.11 are based on two specific expressions for Popt given in [4,Sect. 4], where more general situations are described.…”
Section: (37)mentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 3.3 and 3.11 are examples for the application of the transformed series (2.1). Concerning the generality of this approach we observe that the proof of the theorems consists in finding regions of the complex s-plane where the value Popt for series (2.1) is fully determined by certain "key singularities" of f(s) = S(F) and in showing that nothing changes if in these regions there are more singularities of f. Then we note that the cases of Theorems 3.3 and 3.11 are based on two specific expressions for Popt given in [4,Sect. 4], where more general situations are described.…”
Section: (37)mentioning
confidence: 99%
“…4 [4,8,12], where it is shown that the value Popt may be determined when the locations of the singularities of the function represented by the series to be transformed are known.…”
Section: The New Transformationmentioning
confidence: 99%
“…Recently, several authors (see, for example, Gabutti and Lyness [3], Mathis and Sismondi [8], and Srivastava [19]) investigated many different families of generating functions associated with the Stirling numbers S n k defined by (3.1). We choose to recall here one of Srivastava's general results on these families of generating functions as Then, in terms of the Stirling numbers S n k defined by (3.1), the following family of generating functions,…”
Section: Generating Functions Involving Stirling Numbers Of the Seconmentioning
confidence: 99%
“…The first condition (17) has been obtained from f (∞) = 0, and the second one from f (0) = f w and f (0) = 1. The wall shear stress S is obtained in this approach as…”
Section: The Merkin Transformationmentioning
confidence: 99%
“…(26) and (27) can be accelerated with the aid of the classical Euler-Knopp type series transformation [16]. In the present calculations, following the work of [17], an improved form of the Euler-Knopp transformation has been used. Applied, e.g., to the series (21), the transformation of Gabutti and Lyness gives…”
Section: The Series Solutionmentioning
confidence: 99%